KEMAMPUAN MATEMATIKA DAN RELEVANSINYA DENGAN KUANTITAS DAN KUALITAS HAFALAN ALQURAN PESERTA DIDIK - Yosita, Elmissyar (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2021)
Students at MTs Negeri 1 Pasaman are directed to have a good and high memorization of the Qur'an in quality. The briefing has relevance to the skills needed from students in MTs, in line with previous research proving that the ability of the field of exorcist has an influence on social abilities. Therefore, this study aims to reveal how the relevance of mathematical ability with the quality and quantity of memorization of the Qur'an of learners. This research is designed with quantitative approach, the type of quantitative chosen here is correlation. The results showed that mathematical ability has a positive impact on the quality (Y1) of memorization of the Qur'an, amounting to 11.3%. The results of the study variable memorization test of mathematical ability (X) quality memorization (Y2) had an effect of 1.5 %.